Solid electrolyte coated graphite composite material as well as preparation method and application thereof

By coating the negative electrode material of the lithium-doped conductive agent solid electrolyte on the lithium-ion battery, the problem of insufficient fast charging and cycling performance of lithium-ion batteries is solved, and higher battery performance and longer service life are achieved.

CN119481244APending Publication Date: 2025-02-18SHENZHEN GOLD MEDAL NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411038187.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During the charging and discharging process, the negative electrode materials of existing lithium-ion batteries have a limited improvement in fast charging performance and a decrease in cycle performance.

Method used

The graphite composite material is coated with solid electrolyte, and the electronic and ionic conductivity of the material is improved by coating the solid electrolyte composite of lithium-doped conductive agent outside the graphite core.

Benefits of technology

It improves the fast charging and cycling performance of lithium-ion batteries, enhances the transmission rate of lithium-ion and electronic transmission rate, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481244A_ABST
    Figure CN119481244A_ABST
Patent Text Reader

Abstract

The invention discloses a solid electrolyte coated graphite composite material as well as a preparation method and application thereof. The solid electrolyte coated graphite composite material comprises a graphite inner core and a shell coated outside the graphite inner core. The solid electrolyte coated graphite composite material comprises a graphite inner core and a shell coated outside the graphite inner core, the material of the shell comprises a lithium-doped conductive agent solid electrolyte complex, the lithium-doped conductive agent solid electrolyte complex comprises a lithium-doped solid electrolyte and a conductive agent which are uniformly mixed, and the electron transmission rate of the solid electrolyte is improved by adding lithium doping and the conductive agent; the shell not only utilizes the characteristic of high lithium ion transmission rate and relatively high electron transmission rate of the solid electrolyte, but also can be used as a medium to improve the transmission rate of lithium ions, so that the fast charging performance of the solid electrolyte coated graphite composite material can be improved; the solid electrolyte coated graphite composite material disclosed by the invention is better in fast charging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of secondary batteries, and in particular to a solid electrolyte coated graphite composite material and a preparation method and application thereof. Background Art

[0002] As a green and environmentally friendly new energy, lithium-ion batteries have the advantages of good reliability, high safety, small size and light weight. They have been widely used in digital products, electric vehicles, military products and other fields. With the vigorous development of the new energy industry, the development of lithium-ion batteries is in full swing, but the requirements for the service life, safety and low cost of lithium-ion batteries are also getting higher and higher. At present, lithium-ion batteries are also developing in the direction of long life, high safety, high rate and low cost.

[0003] The negative electrode material is one of the key factors that restrict the energy density and rate charge and discharge performance of lithium-ion batteries. The negative electrode materials used in energy storage batteries are mainly selected from raw materials with high isotropy, artificial graphite materials with low specific surface area and low expansion. However, as the new SEI film expands during the cycle, it consumes lithium ions, causing the cycle performance to decrease during the charge and discharge process.

[0004] Compared with natural graphite negative electrode materials, artificial graphite negative electrode materials have better performance. At present, the market-oriented fast-charging negative electrode materials are mainly artificial graphite, and their surfaces are mainly coated with soft carbon or hard carbon to improve the fast charging and low-temperature performance of the materials. The layered structure of the soft carbon or hard carbon itself causes the electronic and ionic conductivity of the materials to be poor. The lithium ion diffusion coefficient of the coating layer is low during the charging and discharging process, resulting in limited improvement in its fast-charging performance. Solid electrolytes can improve the ionic conductivity of materials as a coating material with their advantages of high ionic conductivity, stable structure, and high safety. However, the electronic conductivity of the solid electrolyte itself is poor, and coating it on the graphite surface has limited effect on improving the fast-charging performance of the material. Summary of the invention

[0005] Based on this, it is necessary to provide a solid electrolyte-coated graphite composite material with better fast charging performance.

[0006] In addition, it is also necessary to provide a method for preparing the above-mentioned solid electrolyte coated graphite composite material and an application of the above-mentioned solid electrolyte coated graphite composite material.

[0007] A solid electrolyte coated graphite composite material, comprising a graphite core and a shell coated outside the core;

[0008] The material of the graphite core is heteroatom-doped graphite, and the material of the shell includes a lithium-doped conductive agent solid electrolyte complex, wherein the lithium-doped conductive agent solid electrolyte complex includes a uniformly mixed lithium-doped solid electrolyte and a conductive agent; the mass ratio of the graphite core to the shell is 92-98:2-8.

[0009] In one embodiment, the outer shell includes 1 wt%-5 wt% of the conductive agent, 10 wt%-80 wt% of the lithium-doped solid electrolyte, and the balance of amorphous carbon.

[0010] In one embodiment, in the lithium-doped solid electrolyte, the mass ratio of lithium to solid electrolyte is 0.3 to 3:100.

[0011] In one embodiment, the conductive agent is selected from at least one of carbon nanotubes, graphene, carbon black and carbon fiber;

[0012] The solid electrolyte is Li 0.36 La 0.51 TiO3 and Li 6.4 La3Ta 0.6 Zr 1.4 O 12 At least one of;

[0013] The heteroatom is at least one of N, B and P.

[0014] A method for preparing the above-mentioned solid electrolyte coated graphite composite material comprises the following steps:

[0015] Adding lithium powder, conductive agent solution and solid electrolyte to an organic solvent, mixing and dispersing the mixture evenly, and carbonizing the mixture after first spray drying to obtain a lithium-doped conductive agent solid electrolyte composite, wherein the lithium-doped conductive agent solid electrolyte composite comprises a lithium-doped solid electrolyte and a conductive agent mixed together;

[0016] The lithium-doped conductive agent solid electrolyte complex, asphalt solution, heteroatom compound and graphite are mixed and dispersed evenly, spray-dried for a second time and carbonized again to obtain the required solid electrolyte-coated graphite composite material, wherein the solid electrolyte-coated graphite composite material includes a graphite core and a shell coated outside the core, the material of the graphite core is heteroatom-doped graphite, the material of the shell includes the lithium-doped conductive agent solid electrolyte complex, and the mass ratio of the graphite core to the shell is 92-98:2-8.

[0017] In one embodiment, the lithium powder, the conductive agent solution and the solid electrolyte are added to the organic solvent and mixed and dispersed evenly, and in the operation of carbonization after the first spray drying, the mass ratio of the lithium powder, the organic solvent, the conductive agent solution and the solid electrolyte is 0.3-3:100-500:10-50:100, the carbonization temperature is 1000°C-1300°C, and the carbonization time is 1h-6h.

[0018] In one embodiment, the organic solvent is selected from at least one of cyclohexane, n-hexane and paraffin;

[0019] The solute of the conductive agent solution is selected from at least one of carbon nanotubes, graphene, carbon black and carbon fiber, the solvent of the conductive agent solution is N-methylpyrrolidone, and the concentration of the conductive agent solution is 5wt%;

[0020] The solid electrolyte is Li 0.36 La 0.51 TiO3 and Li 6.4 La3Ta 0.6 Zr 1.4 O 12 At least one of .

[0021] In one embodiment, the lithium-doped conductive agent solid electrolyte complex, asphalt solution, heteroatom compound and graphite are mixed and dispersed evenly, and in the operation of re-carbonization after a second spray drying, the mass ratio of the lithium-doped conductive agent solid electrolyte complex, the solute of the asphalt solution, the heteroatom compound and the graphite is 5-10:1-5:1-5:100, the re-carbonization temperature is 1200℃-1500℃, and the re-carbonization time is 1h-6h.

[0022] In one embodiment, the solute of the asphalt solution is selected from at least one of petroleum asphalt and coal asphalt, the solvent of the asphalt solution is selected from at least one of benzene, xylene, acetone and chloroform, and the concentration of the asphalt solution is 10wt%-30wt%;

[0023] The heteroatom compound is selected from at least one of ammonia water, boric acid, phosphoric acid and urea.

[0024] Application of the above-mentioned solid electrolyte coated graphite composite material in the field of energy storage devices.

[0025] The solid electrolyte coated graphite composite material of the present invention includes a graphite core and a shell coated outside the graphite core; the material of the shell includes a lithium-doped conductive agent solid electrolyte composite, and the lithium-doped conductive agent solid electrolyte composite includes a uniformly mixed lithium-doped solid electrolyte and a conductive agent. The addition of lithium doping and conductive agent improves the electron transmission rate of the solid electrolyte. This shell not only has the high lithium ion transmission rate characteristics of the solid electrolyte itself, but also has a higher electron transmission rate, and can act as a medium to improve the transmission rate of lithium ions, thereby improving the fast charging performance of the solid electrolyte coated graphite composite material.

[0026] Compared with traditional solid electrolyte coated graphite materials, the solid electrolyte coated graphite composite material of the present invention has better fast charging performance.

[0027] In addition, the shell of the solid electrolyte-coated graphite composite material of the present invention contains a lithium-doped solid electrolyte, which also allows lithium ions to be formed during the initial charge and discharge process, thereby improving the initial efficiency of the composite material and its lithium ion diffusion rate.

[0028] Preferably, the shell of the solid electrolyte-coated graphite composite material of the present invention also includes amorphous carbon, and the material of the graphite core is heteroatom-doped graphite. The heteroatom-doped graphite and amorphous carbon improve the electronic conductivity of the composite material and exert a synergistic effect between the two to improve the power performance and cycle performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] in:

[0031] Figure 1 The present invention is a flow chart of a method for preparing a solid electrolyte-coated graphite composite material according to one embodiment.

[0032] Figure 2 This is a SEM image of the solid electrolyte-coated graphite composite material prepared in Example 1. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the present invention, the descriptions involving "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0035] The invention discloses a solid electrolyte coated graphite composite material according to an embodiment of the invention, comprising a graphite core and a shell coated outside the graphite core.

[0036] The material of the graphite core is heteroatom-doped graphite, and the material of the shell includes a lithium-doped conductive agent solid electrolyte complex, which includes a uniformly mixed lithium-doped solid electrolyte and a conductive agent. The mass ratio of the graphite core to the shell is 92-98:2-8.

[0037] The solid electrolyte coated graphite composite material of the present invention comprises a graphite core and a shell coated outside the graphite core. The material of the shell comprises a lithium-doped conductive agent solid electrolyte composite, the lithium-doped conductive agent solid electrolyte composite comprises a uniformly mixed lithium-doped solid electrolyte and a conductive agent, the lithium doping and the addition of the conductive agent improve the electron transmission rate of the solid electrolyte, the shell not only has the characteristics of the high lithium ion transmission rate of the solid electrolyte itself, but also has a high electron transmission rate, and can be used as a medium to improve the transmission rate of lithium ions, thereby improving the fast charging performance of the solid electrolyte coated graphite composite material.

[0038] Compared with traditional solid electrolyte coated graphite materials, the solid electrolyte coated graphite composite material of the present invention has better fast charging performance.

[0039] In addition, the shell of the solid electrolyte-coated graphite composite material of the present invention contains a lithium-doped solid electrolyte, which also allows lithium ions to be formed during the initial charge and discharge process, thereby improving the initial efficiency of the composite material and its lithium ion diffusion rate.

[0040] Preferably, in this embodiment, the shell includes 1wt%-5wt% of a conductive agent, 10wt%-80wt% of a lithium-doped solid electrolyte, and the remainder of amorphous carbon.

[0041] The outer shell of the solid electrolyte-coated graphite composite material of the present invention also includes amorphous carbon, and the material of the graphite core is heteroatom-doped graphite. The heteroatom-doped graphite and amorphous carbon improve the electronic conductivity of the composite material and exert a synergistic effect between the two to improve the power performance and cycle performance of the material.

[0042] Preferably, in this embodiment, in the lithium-doped solid electrolyte, the mass ratio of lithium to the solid electrolyte is 0.3 to 3:100.

[0043] More preferably, in this embodiment, in the lithium-doped solid electrolyte, the mass ratio of lithium to the solid electrolyte is 1:100.

[0044] Specifically, in the present embodiment, the conductive agent is selected from at least one of carbon nanotubes, graphene, carbon black and carbon fibers.

[0045] Carbon nanotubes are tubular structures composed of carbon atoms, with many excellent physical and chemical properties, among which electrical conductivity is one of its most notable features. Since carbon nanotubes have extremely small diameters and high specific surface areas, their electrons move freely inside the tubes, forming a one-dimensional conductive channel, thus showing excellent electrical conductivity and electron mobility. The electrical conductivity of carbon nanotubes can be more than 10 times that of copper and more than 1,000 times that of silver.

[0046] Graphene, as a new type of two-dimensional layered carbon material, has a high aspect ratio and excellent hydrophobicity, thermal conductivity and chemical stability. The conjugated system makes its electronic conduction ability very strong and has excellent electrical conductivity.

[0047] Carbon black is a semiconductor material. The microstructure of carbon black gives carbon black conductivity. The conductivity of carbon black is closely related to its microstructure, particle size, structure, surface properties, etc. Generally speaking, the smaller the carbon black particles, the better the conductivity. This is because increasing the number of carbon black particles per unit volume increases the contact points or reduces the distance between particles in the dispersed system, which reduces the resistance and increases the conductivity. Fine particle carbon black has high conductivity.

[0048] Carbon fiber is a highly conductive material with excellent comprehensive performance and many unparalleled advantages over other materials. In addition to its high conductivity, it is also corrosion-resistant, wear-resistant, high-temperature-resistant, high-strength, and light-weight, and is widely used.

[0049] Specifically, in this embodiment, the solid electrolyte is Li 0.36 La 0.51 TiO3 and Li 6.4 La3Ta 0.6 Zr 1.4 O 12 At least one of .

[0050] Specifically, in this embodiment, the heteroatom is at least one of N, B and P.

[0051] Heteroatom-doped graphite increases the electronic conductivity of the material, reduces the irreversible capacity, and improves the initial efficiency due to the doping of heteroatoms N, B, and P, which are located at the defects of the carbon ring.

[0052] Combination Figure 1 The present invention also discloses a method for preparing the above-mentioned solid electrolyte-coated graphite composite material in an embodiment, comprising the following steps:

[0053] S10, adding lithium powder, conductive agent solution and solid electrolyte to an organic solvent, mixing and dispersing them uniformly, and carbonizing them after the first spray drying to obtain a lithium-doped conductive agent solid electrolyte composite.

[0054] The lithium-doped conductive agent solid electrolyte composite comprises a lithium-doped solid electrolyte and a conductive agent mixed together.

[0055] It should be noted that in S10, in the carbonization operation after the first spray drying, the carbonization operation needs to be performed under a protective gas atmosphere. The protective gas atmosphere can be a nitrogen atmosphere, a helium atmosphere, a neon atmosphere, an argon atmosphere, etc.

[0056] Spray drying allows the dispersed system to be atomized and contacted with hot air, causing the solvent to vaporize rapidly and dry, thereby quickly preparing a powdered product, eliminating traditional evaporation, crushing and other processes.

[0057] Specifically, in this embodiment, the operation of adding lithium powder, conductive agent solution and solid electrolyte to organic solvent and dispersing them evenly after mixing is as follows: lithium powder is added to organic solvent to dissolve, then conductive agent solution is added and dispersed evenly, and finally solid electrolyte is added and dispersed evenly, and the above operations are completed after filtering.

[0058] During the formation process of lithium-ion batteries, SEI growth on the negative electrode surface consumes active lithium, resulting in battery energy loss, which in turn causes problems such as low first-cycle efficiency and poor cycle life. The addition of lithium powder can make up for the lithium loss during the first cycle to improve the first-cycle efficiency and life. The addition of lithium powder can compensate for the loss of active lithium, improve the defect of low first-cycle efficiency of negative electrode materials, give full play to its high capacity advantages, improve battery energy density and extend cycle life.

[0059] Preferably, in this embodiment, lithium powder, conductive agent solution and solid electrolyte are added to an organic solvent and mixed and then dispersed evenly. In the carbonization operation after the first spray drying, the mass ratio of lithium powder, organic solvent, conductive agent solution and solid electrolyte is 0.3-3:100-500:10-50:100, the carbonization temperature is 1000°C-1300°C, and the carbonization time is 1h-6h.

[0060] More preferably, the mass ratio of lithium powder, organic solvent, conductive agent solution and solid electrolyte is 1:100-500:10-50:100

[0061] Specifically, in this embodiment, the organic solvent is at least one selected from cyclohexane, n-hexane and paraffin.

[0062] Specifically, in this embodiment, the solute of the conductive agent solution is selected from at least one of carbon nanotubes, graphene, carbon black and carbon fiber, the solvent of the conductive agent solution is N-methylpyrrolidone, and the concentration of the conductive agent solution is 5wt%.

[0063] Carbon nanotubes are tubular structures composed of carbon atoms, with many excellent physical and chemical properties, among which electrical conductivity is one of its most notable features. Since carbon nanotubes have extremely small diameters and high specific surface areas, their electrons move freely inside the tubes, forming a one-dimensional conductive channel, thus showing excellent electrical conductivity and electron mobility. The electrical conductivity of carbon nanotubes can be more than 10 times that of copper and more than 1,000 times that of silver.

[0064] Graphene, as a new type of two-dimensional layered carbon material, has a high aspect ratio and excellent hydrophobicity, thermal conductivity and chemical stability. The conjugated system makes its electronic conduction ability very strong and has excellent electrical conductivity.

[0065] Carbon black is a semiconductor material. The microstructure of carbon black gives carbon black conductivity. The conductivity of carbon black is closely related to its microstructure, particle size, structure, surface properties, etc. Generally speaking, the smaller the carbon black particles, the better the conductivity. This is because increasing the number of carbon black particles per unit volume increases the contact points or reduces the distance between particles in the dispersed system, which reduces the resistance and increases the conductivity. Fine particle carbon black has high conductivity.

[0066] Carbon fiber is a highly conductive material with excellent comprehensive performance and many unparalleled advantages over other materials. In addition to its high conductivity, it is also corrosion-resistant, wear-resistant, high-temperature-resistant, high-strength, and light-weight, and is widely used.

[0067] Specifically, in this embodiment, the solid electrolyte is Li 0.36 La 0.51 TiO3 and Li 6.4 La3Ta 0.6 Zr 1.4 O 12 At least one of .

[0068] It should be pointed out that in S10, the lithium powder doped in the solid electrolyte is converted into lithium oxide during the carbonization operation, and the doping of lithium oxide improves the electron transfer rate and lithium ion transfer rate of the solid electrolyte.

[0069] It should be noted that in S10, the solvent of the conductive agent solution is converted into amorphous carbon during the carbonization operation, so that the lithium-doped conductive agent solid electrolyte composite also contains amorphous carbon.

[0070] It should be pointed out that the lithium-doped conductive agent solid electrolyte composite prepared in S10 serves as the outer shell of the finally prepared composite material. The lithium-doped conductive agent solid electrolyte composite includes a uniformly mixed lithium-doped solid electrolyte and a conductive agent. The addition of lithium doping and the conductive agent improves the electron transmission rate of the solid electrolyte. The outer shell of this material not only has the high lithium ion transmission rate of the solid electrolyte itself, but also has a high electron transmission rate, and can serve as a medium to improve the transmission rate of lithium ions, thereby improving the fast charging performance of the solid electrolyte-coated graphite composite material.

[0071] In addition, the shell containing the lithium-doped solid electrolyte also allows the composite material to form lithium ions during the initial charge and discharge process, thereby improving the initial efficiency of the composite material and its lithium ion diffusion rate.

[0072] S20, mixing the lithium-doped conductive agent solid electrolyte composite, the asphalt solution, the heteroatom compound and the graphite and dispersing them uniformly, spray drying them for the second time and carbonizing them again to obtain the desired solid electrolyte-coated graphite composite material.

[0073] Among them, the solid electrolyte coated graphite composite material includes a graphite core and an outer shell coated outside the graphite core, the material of the graphite core is heteroatom-doped graphite, the material of the outer shell includes a lithium-doped conductive agent solid electrolyte composite, and the mass ratio of the graphite core and the outer shell is 92-98:2-8.

[0074] It should be noted that in S20, the re-carbonization operation after the second spray drying needs to be performed under a protective gas atmosphere. The protective gas atmosphere can be a nitrogen atmosphere, a helium atmosphere, a neon atmosphere, an argon atmosphere, etc.

[0075] Spray drying allows the dispersed system to be atomized and contacted with hot air, causing the solvent to vaporize rapidly and achieve drying, thereby quickly preparing a powdered product, eliminating traditional evaporation, crushing and other processes.

[0076] Specifically, in this embodiment, the operation of mixing and dispersing the lithium-doped conductive agent solid electrolyte complex, asphalt solution, heteroatom compound and graphite uniformly is as follows: adding the lithium-doped conductive agent solid electrolyte complex to the asphalt solution, then adding the heteroatom compound, and finally adding graphite and dispersing it uniformly.

[0077] Preferably, in this embodiment, the lithium-doped conductive agent solid electrolyte complex, asphalt solution, heteroatom compound and graphite are mixed and dispersed evenly, and in the re-carbonization operation after the second spray drying, the mass ratio of the lithium-doped conductive agent solid electrolyte complex, the solute of the asphalt solution, the heteroatom compound and graphite is 5-10:1-5:1-5:100, the re-carbonization temperature is 1200℃-1500℃, and the re-carbonization time is 1h-6h.

[0078] Specifically, in this embodiment, the solute of the asphalt solution is selected from at least one of petroleum asphalt and coal asphalt, the solvent of the asphalt solution is selected from at least one of benzene, xylene, acetone and chloroform, and the concentration of the asphalt solution is 10wt%-30wt%.

[0079] During the carbonization process of asphalt, a stable amorphous carbon structure is formed due to the volatilization of its own moisture and volatile components. The asphalt itself has bonding function and good fluidity, which plays a dispersing and bonding function, improving the isotropy of the material and the uniformity of its carbon coating.

[0080] Specifically, in this embodiment, the heteroatom compound is selected from at least one of ammonia water, boric acid, phosphoric acid and urea.

[0081] The addition of the heteroatom compound makes the graphite core material of the final composite material to be heteroatom-doped graphite.

[0082] Heteroatom-doped graphite improves the electronic conductivity of the material, reduces the irreversible capacity, and improves the initial efficiency due to the doping of heteroatoms N, B, and P, which are located at the defects of the carbon ring.

[0083] Specifically, compounds such as ammonia, boric acid, phosphoric acid, and urea can achieve doping of heteroatoms such as N, B, and P.

[0084] Combined with S10, the shell also includes amorphous carbon, and the material of the graphite core is heteroatom-doped graphite. The heteroatom-doped graphite and amorphous carbon improve the electronic conductivity of the composite material and exert a synergistic effect between the two to improve the power performance of the material and its cycle performance.

[0085] The preparation method of the solid electrolyte coated graphite composite material of the present invention, the prepared solid electrolyte coated graphite composite material includes a graphite core and a shell coated outside the graphite core. The material of the shell includes a lithium-doped conductive agent solid electrolyte composite, the lithium-doped conductive agent solid electrolyte composite includes a uniformly mixed lithium-doped solid electrolyte and a conductive agent, the lithium doping and the addition of the conductive agent improve the electron transmission rate of the solid electrolyte, the shell not only has the characteristics of the high lithium ion transmission rate of the solid electrolyte itself, but also has a higher electron transmission rate, and can be used as a medium to improve the transmission rate of lithium ions, thereby improving the fast charging performance of the solid electrolyte coated graphite composite material.

[0086] Compared with traditional solid electrolyte coated graphite materials, the method for preparing the solid electrolyte coated graphite composite material of the present invention has better fast charging performance of the prepared solid electrolyte coated graphite composite material.

[0087] In addition, the preparation method of the solid electrolyte-coated graphite composite material of the present invention, the shell of the obtained solid electrolyte-coated graphite composite material contains a lithium-doped solid electrolyte, and lithium ions can be formed during the initial charge and discharge process, thereby improving the initial efficiency of the composite material and its lithium ion diffusion rate.

[0088] The preparation method of the solid electrolyte coated graphite composite material of the present invention, the shell of the prepared solid electrolyte coated graphite composite material also includes amorphous carbon, the material of the graphite core is heteroatom-doped graphite, the heteroatom-doped graphite and amorphous carbon improve the electronic conductivity of the composite material, and exert the synergistic effect between the two, thereby improving the power performance and cycle performance of the material.

[0089] The invention also discloses the application of the solid electrolyte coated graphite composite material in the field of energy storage devices.

[0090] For example, the solid electrolyte-coated graphite composite material can be applied in the field of secondary batteries.

[0091] Specifically, the solid electrolyte-coated graphite composite material can be used as a negative electrode material for lithium-ion secondary batteries.

[0092] In addition, the above-mentioned solid electrolyte-coated graphite composite material can also be applied to fields such as supercapacitors.

[0093] The following are specific embodiments.

[0094] The sources of key raw materials are as follows:

[0095] Metal lithium powder: Tianjin Zhongneng Lithium Industry Co., Ltd.; Model: passivated lithium powder;

[0096] Petroleum asphalt: Manufacturer: Liaoning Xinde New Materials Technology Co., Ltd.; Model: 250#;

[0097] Coal tar pitch: Baowu Carbon Industry Co., Ltd.; Model: BW-D-402;

[0098] Artificial graphite: Shanghai Shanshan Technology Co., Ltd.; Model: QC-8.

[0099] Example 1

[0100] A method for preparing a solid electrolyte-coated graphite composite material comprises the following steps:

[0101] 1g of lithium metal powder was added to 300g of cyclohexane organic solvent for dissolution, then 30g of 5wt% carbon nanotube conductive agent N-methylpyrrolidone solution was added for uniform dispersion, and 100g of Li 0.36 La 0.51 The TiO3 is evenly dispersed, filtered, and spray-dried, and then the obtained material is transferred to a tube furnace and heated to 1200°C for carbonization for 3 hours under a nitrogen atmosphere to obtain a lithium-doped conductive agent solid electrolyte composite;

[0102] 8g of lithium-doped conductive agent solid electrolyte composite is added to 30g of 20wt% petroleum asphalt xylene solvent, and 3g of boric acid is added, and then 100g of artificial graphite is added and dispersed evenly, spray dried, and then transferred to a tube furnace, heated to 1250°C in a nitrogen atmosphere and carbonized for 3h to obtain a solid electrolyte coated graphite composite material. The prepared solid electrolyte coated graphite composite material includes a graphite core and a shell coated outside the graphite core, the material of the graphite core is heteroatom-doped graphite, and the material of the shell includes the lithium-doped conductive agent solid electrolyte composite.

[0103] Example 2

[0104] A method for preparing a solid electrolyte-coated graphite composite material comprises the following steps:

[0105] 0.3g of lithium metal powder was added to 100g of paraffin organic solvent to dissolve, and then 10g of N-methylpyrrolidone solution of graphene conductive agent with a concentration of 5wt% was added to disperse evenly, and 100g of Li 6.4 La3Ta 0.6 Zr 1.4 O 12 The obtained material is uniformly dispersed, filtered, and spray-dried, and then transferred to a tube furnace, heated to 1000° C. in a nitrogen atmosphere and carbonized for 6 hours to obtain a lithium-doped conductive agent solid electrolyte composite;

[0106] 5g of lithium-doped conductive agent solid electrolyte composite is added to 10g of 10wt% coal tar acetone solution, and 1g of ammonia water is added, and then 100g of artificial graphite is added and dispersed evenly, spray dried, and then transferred to a tube furnace, heated to 1200°C in a nitrogen atmosphere and carbonized for 6h to obtain a solid electrolyte coated graphite composite material. The prepared solid electrolyte coated graphite composite material includes a graphite core and a shell coated outside the graphite core, the material of the graphite core is heteroatom-doped graphite, and the material of the shell includes the lithium-doped conductive agent solid electrolyte composite.

[0107] Example 3

[0108] A method for preparing a solid electrolyte-coated graphite composite material comprises the following steps:

[0109] 3g of lithium metal powder was added to 500g of cyclohexane organic solvent to dissolve, then 50g of 5wt% carbon black N-methylpyrrolidone solution was added to disperse evenly, and 100g of Li 6.4 La3Ta 0.6 Zr 1.4 O 12 The mixture was evenly dispersed, filtered, spray dried, and then transferred to a tube furnace and heated to 1300° C. for carbonization for 1 h in a nitrogen atmosphere to obtain a lithium-doped conductive agent solid electrolyte composite.

[0110] 10g of lithium-doped conductive agent solid electrolyte composite is added to 16.6g of 30wt% petroleum asphalt in chloroform solvent, and 5g of urea is added, and then 100g of artificial graphite is added and dispersed evenly, spray dried, and then transferred to a tube furnace, heated to 1500°C in a nitrogen atmosphere and carbonized for 1h to obtain a solid electrolyte coated graphite composite material. The prepared solid electrolyte coated graphite composite material includes a graphite core and a shell coated outside the graphite core, the material of the graphite core is heteroatom-doped graphite, and the material of the shell includes the lithium-doped conductive agent solid electrolyte composite.

[0111] Example 4

[0112] A method for preparing a solid electrolyte-coated graphite composite material comprises the following steps:

[0113] 0.3 g of lithium metal powder was added to 500 g of cyclohexane organic solvent for dissolution, and then 10 g of 5 wt% carbon nanotube conductive agent N-methylpyrrolidone solution was added to disperse evenly, and 100 g of Li 0.36 La 0.51 The TiO3 is evenly dispersed, filtered, and spray-dried, and then the obtained material is transferred to a tube furnace and heated to 1200°C for carbonization for 3 hours under a nitrogen atmosphere to obtain a lithium-doped conductive agent solid electrolyte composite;

[0114] 8g of lithium-doped conductive agent solid electrolyte composite is added to 30g of 20wt% petroleum asphalt xylene solvent, and 3g of boric acid is added, and then 100g of artificial graphite is added and dispersed evenly, spray dried, and then transferred to a tube furnace, heated to 1250°C in a nitrogen atmosphere and carbonized for 3h to obtain a solid electrolyte coated graphite composite material. The prepared solid electrolyte coated graphite composite material includes a graphite core and a shell coated outside the graphite core, the material of the graphite core is heteroatom-doped graphite, and the material of the shell includes the lithium-doped conductive agent solid electrolyte composite.

[0115] Example 5

[0116] A method for preparing a solid electrolyte-coated graphite composite material comprises the following steps:

[0117] 3g of lithium metal powder was added to 100g of cyclohexane organic solvent for dissolution, and then 50g of 5wt% carbon nanotube conductive agent N-methylpyrrolidone solution was added to disperse evenly, and 100g of Li 0.36 La 0.51 The TiO3 is evenly dispersed, filtered, and spray-dried, and then the obtained material is transferred to a tube furnace and heated to 1200°C for carbonization for 3 hours under a nitrogen atmosphere to obtain a lithium-doped conductive agent solid electrolyte composite;

[0118] 8g of lithium-doped conductive agent solid electrolyte composite is added to 30g of 20wt% petroleum asphalt in xylene solvent, and 3g of boric acid is added, and then 100g of artificial graphite is added and dispersed evenly, spray dried, and then transferred to a tube furnace, heated to 1250°C in a nitrogen atmosphere and carbonized for 3h to obtain a solid electrolyte coated graphite composite material. The prepared solid electrolyte coated graphite composite material includes a graphite core and a shell coated outside the graphite core, the material of the graphite core is heteroatom-doped graphite, and the material of the shell includes the lithium-doped conductive agent solid electrolyte composite.

[0119] Comparative Example 1

[0120] Comparative Example 1 is substantially the same as the embodiment, except that Li is not added in Comparative Example 1. 0.36 La 0.51 TiO3 solid electrolyte.

[0121] 1 g of metallic lithium powder was added to 300 g of cyclohexane organic solvent for dissolution, and then 30 g of 5 wt% carbon nanotube conductive agent N-methylpyrrolidone solution was added for uniform dispersion, filtered, and spray dried. Then, the obtained material was transferred to a tube furnace and heated to 1200° C. in a nitrogen atmosphere for carbonization for 3 h to obtain a lithium-doped conductive agent composite;

[0122] 8g of lithium-doped conductive agent composite is added to 30g of xylene solvent containing 20wt% petroleum asphalt, and 3g of boric acid is added, followed by adding 100g of artificial graphite to disperse evenly, spray drying, and then transferred to a tube furnace, heated to 1250°C in a nitrogen atmosphere and carbonized for 3h to obtain a lithium-doped conductive agent-coated graphite composite material. The prepared lithium-doped conductive agent-coated graphite composite material includes a graphite core and a shell coated outside the graphite core, the material of the graphite core is heteroatom-doped graphite, and the material of the shell includes a lithium-doped conductive agent.

[0123] Comparative Example 2

[0124] Comparative Example 2 is substantially the same as the embodiment, except that lithium powder and cyclohexane organic solvent are not added in Comparative Example 2.

[0125] 100 g of Li was added to 30 g of a 5 wt% carbon nanotube conductive agent in N-methylpyrrolidone. 0.36 La 0.51 The TiO3 is evenly dispersed, filtered, and spray-dried, and then the obtained material is transferred to a tube furnace and heated to 1200°C for carbonization for 3 hours under a nitrogen atmosphere to obtain a conductive agent-doped solid electrolyte composite;

[0126] 8g of the conductive agent doped solid electrolyte composite is added to 30g of a xylene solvent containing 20wt% petroleum asphalt, and 3g of boric acid is added, followed by adding 100g of artificial graphite to disperse evenly, spray drying, and then transferring to a tubular furnace, heating to 1250°C under a nitrogen atmosphere and carbonizing for 3h to obtain a solid electrolyte coated graphite composite material. The prepared solid electrolyte coated graphite composite material includes a graphite core and a shell coated outside the graphite core, the material of the graphite core is heteroatom-doped graphite, and the material of the shell includes the conductive agent doped solid electrolyte composite.

[0127] Comparative Example 3

[0128] Comparative Example 3 is substantially the same as the embodiment, except that no boric acid is added in Comparative Example 3.

[0129] 1g of lithium metal powder was added to 300g of cyclohexane organic solvent for dissolution, then 30g of 5wt% carbon nanotube conductive agent N-methylpyrrolidone solution was added for uniform dispersion, and 100g of Li 0.36 La 0.51 The TiO3 is evenly dispersed, filtered, and spray-dried, and then the obtained material is transferred to a tube furnace and heated to 1200°C for carbonization for 3 hours under a nitrogen atmosphere to obtain a lithium-doped conductive agent solid electrolyte composite;

[0130] 8g of lithium-doped conductive agent solid electrolyte composite is added to 30g of 20wt% petroleum asphalt in xylene solvent, and then 100g of artificial graphite is added to disperse evenly, spray dried, and then transferred to a tube furnace and heated to 1250°C in a nitrogen atmosphere for carbonization for 3h to obtain a solid electrolyte coated graphite composite material. The prepared solid electrolyte coated graphite composite material includes a graphite core and a shell coated outside the graphite core, the material of the graphite core is heteroatom-doped graphite, and the material of the shell includes the lithium-doped conductive agent solid electrolyte composite.

[0131] Test Case

[0132] (1) SEM test

[0133] The solid electrolyte coated graphite composite material prepared in Example 1 was subjected to SEM testing, and the results are as follows: Figure 2 shown.

[0134] Depend on Figure 2 It can be seen that the solid electrolyte-coated graphite composite material prepared in Example 1 presents a single particle structure, with a small amount of micropores on the surface, a particle size between 10 μm and 15 μm, and a uniform size distribution.

[0135] (2) Button battery test

[0136] The solid electrolyte coated graphite composite materials prepared in Examples 1-5, the lithium-doped conductive agent coated graphite composite materials prepared in Comparative Example 1, and the solid electrolyte coated graphite composite materials prepared in Comparative Example 2 and Comparative Example 3 were respectively used as negative electrode materials and assembled into button batteries according to the following methods:

[0137] Add a binder, a conductive agent, and a solvent to the negative electrode material, stir and mix them evenly to form a negative electrode slurry, coat the negative electrode slurry on a copper foil, dry, roll, and cut to obtain a negative electrode sheet. The binder is polyvinylidene fluoride, the conductive agent is SP conductive agent, the solvent is NMP, and the weight ratio of the negative electrode material, SP conductive agent, polyvinylidene fluoride and NMP is 95:1:4:220. Use a metal lithium sheet as a counter electrode, a polyethylene (PE) film as a diaphragm, and LiPF6 / EC+DEC (the concentration of LiPF6 is 1.3 mol / L, and the volume ratio of EC and DEC is 1:1) as an electrolyte, and assemble the battery in an argon-filled glove box.

[0138] The button cells were installed on a Wuhan Blue Power CT2001A battery tester, and charged and discharged at a rate of 0.1C, with a charge and discharge voltage range of 0.005V to 2.0V, and the first discharge capacity and first discharge efficiency were measured. The battery's charge DCR (50% SOC) and cycle performance (0.1C / 0.1C, 100 weeks) were also tested.

[0139] According to the national standard GB / T-24533-2019 "Graphite Anode Materials for Lithium-ion Batteries", the tap density, specific surface area, powder conductivity and powder OI value of the above-mentioned negative electrode materials were tested, and the test results are shown in Table 1.

[0140] Table 1

[0141]

[0142]

[0143] It can be seen from Table 1 that the discharge specific capacity and DCR of the solid electrolyte-coated graphite composite materials prepared in Examples 1-5 are significantly higher than those in Comparative Examples 1-3; the reason may be that the surface of the solid electrolyte-coated graphite composite materials prepared in Examples 1-5 is coated with a solid electrolyte and its lithium salt, which reduces its irreversible capacity and improves the transmission rate of lithium ions, improves the conductivity and the first efficiency of the solid electrolyte-coated graphite composite materials prepared in Examples 1-5, reduces the DCR and improves the cycle performance.

[0144] (3) Soft pack battery test

[0145] The negative electrode was prepared using the solid electrolyte coated graphite composite material prepared in Examples 1-5, the lithium doped conductive agent coated graphite composite material prepared in Comparative Example 1, and the solid electrolyte coated graphite composite material prepared in Comparative Example 2 and Comparative Example 3 as negative electrode materials, and the ternary material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2) was used as the positive electrode material to prepare the positive electrode, LiPF6 (solvent was EC+DEC, volume ratio was 1:1, concentration was 1.3 mol / L) was used as the electrolyte, and celegard2400 was used as the separator to prepare a 2Ah soft-pack battery.

[0146] When preparing the negative electrode, a binder, a conductive agent, and a solvent are added to the negative electrode material, stirred and mixed to form a negative electrode slurry, and the negative electrode slurry is coated on a copper foil, dried, rolled, and cut to form a negative electrode sheet. The binder is LA132 binder, the conductive agent is SP conductive agent, the solvent is double distilled water, and the weight ratio of the negative electrode material, SP conductive agent, LA132 binder and double distilled water is 95:1:4:220.

[0147] 1) Rate performance test

[0148] The charge and discharge voltage range is 2.8V-4.2V, the test temperature is 25±3.0℃, and the charging is performed at 1.0C, 2.0C, 3.0C, and 5.0C, and the discharging is performed at 1.0C. The constant current ratio of the battery under different charging modes is tested, and the results are shown in Table 2.

[0149] Table 2

[0150]

[0151]

[0152] As can be seen from Table 2, the rate charging performance of the soft-pack battery containing the solid electrolyte-coated graphite composite material prepared in Examples 1-5 is significantly better than that of Comparative Examples 1-3, and the charging time is shorter, indicating that the solid electrolyte-coated graphite composite material prepared in Examples 1-5 has good fast charging performance as a negative electrode material. The reason may be that the surface of the solid electrolyte-coated graphite composite material is coated with a solid electrolyte and its lithium salt with high ion conductivity, which improves the ion transfer rate of the material. At the same time, the solid electrolyte-coated graphite composite material has excellent powder conductivity, which improves the constant current ratio of the solid electrolyte-coated graphite composite material.

[0153] 2) Cycle performance test

[0154] The following experiment was carried out on soft-pack batteries prepared using the solid electrolyte-coated graphite composite materials prepared in Examples 1-5, the lithium-doped conductive agent-coated graphite composite materials prepared in Comparative Example 1, and the solid electrolyte-coated graphite composite materials prepared in Comparative Example 2 and Comparative Example 3 as negative electrode materials: at a charge and discharge rate of 2C / 2C and a voltage range of 2.8V-4.2V, 100 and 500 charge and discharge cycles were performed sequentially to test the capacity retention rate. The results are shown in Table 3.

[0155] Table 3

[0156]

[0157]

[0158] It can be seen from Table 3 that the cycle performance of the soft-pack battery whose negative electrode contains the solid electrolyte-coated graphite composite material prepared in Example 1-5 is significantly better than that of Comparative Example 1-3 in all stages. The reason may be that the surface of the solid electrolyte-coated graphite composite material prepared in Example 1-5 is coated with a solid electrolyte, which improves the structural stability of the solid electrolyte-coated graphite composite material prepared in Example 1-5. At the same time, the solid electrolyte-coated graphite composite material prepared in Example 1-5 is doped with lithium salt, which provides sufficient lithium salt during the charge and discharge process and improves the cycle performance.

[0159] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A solid electrolyte coated graphite composite material, characterized in that: It comprises a graphite core and a shell covering the graphite core; The material of the graphite core is heteroatom-doped graphite, and the material of the shell includes a lithium-doped conductive agent solid electrolyte complex, wherein the lithium-doped conductive agent solid electrolyte complex includes a uniformly mixed lithium-doped solid electrolyte and a conductive agent; the mass ratio of the graphite core to the shell is 92-98:2-8.

2. The solid electrolyte coated graphite composite material according to claim 1, characterized in that: The outer shell includes 1 wt % to 5 wt % of the conductive agent, 10 wt % to 80 wt % of the lithium-doped solid electrolyte, and the balance of amorphous carbon.

3. The solid electrolyte coated graphite composite material according to claim 2, characterized in that: In the lithium-doped solid electrolyte, the mass ratio of lithium to solid electrolyte is 0.3 to 3:

100.

4. The solid electrolyte-coated graphite composite material according to any one of claims 1 to 3, characterized in that: The conductive agent is selected from at least one of carbon nanotubes, graphene, carbon black and carbon fibers; The solid electrolyte is Li 0.36 La 0.51 TiO3 and Li 6.4 La3Ta 0.6 Zr 1.4 O 12 At least one of; The heteroatom is at least one of N, B and P.

5. A method for preparing a solid electrolyte-coated graphite composite material according to any one of claims 1 to 4, characterized in that: The steps include: Adding lithium powder, conductive agent solution and solid electrolyte to an organic solvent, mixing and dispersing the mixture evenly, and carbonizing the mixture after first spray drying to obtain a lithium-doped conductive agent solid electrolyte composite, wherein the lithium-doped conductive agent solid electrolyte composite comprises a lithium-doped solid electrolyte and a conductive agent mixed together; The lithium-doped conductive agent solid electrolyte complex, asphalt solution, heteroatom compound and graphite are mixed and dispersed evenly, spray-dried for a second time and carbonized again to obtain the required solid electrolyte-coated graphite composite material, wherein the solid electrolyte-coated graphite composite material includes a graphite core and a shell coated outside the core, the material of the graphite core is heteroatom-doped graphite, the material of the shell includes the lithium-doped conductive agent solid electrolyte complex, and the mass ratio of the graphite core to the shell is 92-98:2-8.

6. The method for preparing the solid electrolyte coated graphite composite material according to claim 5, characterized in that: In the operation of adding lithium powder, conductive agent solution and solid electrolyte to an organic solvent, mixing and evenly dispersing, and carbonizing after the first spray drying, the mass ratio of the lithium powder, the organic solvent, the conductive agent solution and the solid electrolyte is 0.3-3:100-500:10-50:100, the carbonization temperature is 1000°C-1300°C, and the carbonization time is 1h-6h.

7. The method for preparing a solid electrolyte-coated graphite composite material according to claim 6, characterized in that: The organic solvent is selected from at least one of cyclohexane, n-hexane and paraffin; The solute of the conductive agent solution is selected from at least one of carbon nanotubes, graphene, carbon black and carbon fiber, the solvent of the conductive agent solution is N-methylpyrrolidone, and the concentration of the conductive agent solution is 5wt%; The solid electrolyte is Li 0.36 La 0.51 TiO3 and Li 6.4 La3Ta 0.6 Zr 1.4 O 12 At least one of .

8. The method for preparing a solid electrolyte-coated graphite composite material according to any one of claims 5 to 7, characterized in that: The lithium-doped conductive agent solid electrolyte complex, asphalt solution, heteroatom compound and graphite are mixed and dispersed evenly, and in the operation of re-carbonization after a second spray drying, the mass ratio of the lithium-doped conductive agent solid electrolyte complex, the solute of the asphalt solution, the heteroatom compound and the graphite is 5-10:1-5:1-5:100, the re-carbonization temperature is 1200℃-1500℃, and the re-carbonization time is 1h-6h.

9. The method for preparing the solid electrolyte coated graphite composite material according to claim 8, characterized in that: The solute of the asphalt solution is selected from at least one of petroleum asphalt and coal asphalt, the solvent of the asphalt solution is selected from at least one of benzene, xylene, acetone and chloroform, and the concentration of the asphalt solution is 10wt%-30wt%; The heteroatom compound is selected from at least one of ammonia water, boric acid, phosphoric acid and urea.

10. Use of the solid electrolyte coated graphite composite material according to any one of claims 1 to 4 in the field of energy storage devices.